Millennial Muslims Intention to Donate Cash Using the Extended Theory of Planned Behavior Approach - Ahmad Aizuddin Hamzah; Galad Mohamed Barre; Anath Rau Krishnan; Abu Bashar; Mohammad Shahfaraz Khan; Iqbal Thonse Hawaldar; Arfi Mulyasa Insani (Tinta Emas Publisher, 2024)
This study aims to understand the factors that influence millennial Muslims in South Tangerang's intention to donate cash, by applying the Extended Theory of Planned Behaviour (ETPB) approach. This research involves analysis using the SmartPLS tool to evaluate the role of attitude, subjective norms, perceived behavioral control, and moral obligation on cash waqf intention. The results show that positive attitudes towards waqf, social environmental influences, self-control, as well as moral responsibility play an important role in shaping cash waqf intentions among millennial Muslims. Attitude towards waqf is influenced by an understanding of the importance of waqf in Islam and the resulting social benefits. Subjective norms are shaped by family support and social environment, while perceived behavioral control is closely related to an individual's belief in his or her ability to endow. In addition, moral obligation shows a significant influence in driving cash waqf intention. This study provides important insights for stakeholders in promoting cash waqf as an integral part of economic and social empowerment in Muslim societies.